Jump Diffusion model for barrier option pricing with stochastic volatility - ALIMANSYAH (NIM: 20915004), ARFIAN
Barrier option is an option which have a certain stock price which is called barrier. If the stockprice of the option reaching or passing the barrier in anytime before the expiry date, the option will be either active (knock-in) or terminated (knock-out). Nonlinear option maeans that the option will have a stochastic volatility. Stochas-tic volaitility is used as an approach to decrease the number of assumption that used in stockpath modelling. For this research, we will try to model barrier option with GARCH volatility using jump-diffusion model. Jump-diffusion model using jump process, which based on poisson process, to model the jumping movement of the stockprice.